From the light blue sky to the dark deep sea: Trophic and resource partitioning between epipelagic and mesopelagic layers in a tropical oceanic ecosystem - Eduardo, Leandro Nolé; Lucena-Frédou, Flávia; Lanco Bertrand, Sophie; Lira, Alex Souza; Mincarone, Michael Maia; Nunes, Guilherme Tavares; Frédou, Thierry; Soares, Andrey; Le Loc'h, François; Pelage, Latifa; Schwamborn, Ralf; Travassos, Paulo; et al. (Elsevier, 2023)
The connection between epipelagic and deep-sea mesopelagic realms controls a variety of ecosystem processes including oceanic carbon storage and the provision of harvestable fish stocks. So far, these two layers have been mostly addressed in isolation and the ways they connect remain poorly understood. Furthermore, both systems are affected by climate change, exploitation of resources, and increasing pervasion of pollutants. Here we use bulk isotopes of δ13C and δ15N of 60 ecosystem components to evaluate the trophic linkage between epipelagic and mesopelagic ecosystems in warm oligotrophic waters. Additionally, we we conducted a comparison of isotopic niche sizes and overlaps across multiple species to evaluate how environmental gradients between epipelagic and mesopelagic ecosystems shape ecological patterns of resource use and competition between species. Our database comprises siphonophores, crustaceans, cephalopods, salpas, fishes, and seabirds. It also includes five zooplankton size classes, two groups of fish larvae, and particulate organic matter collected at different depths. Through this wide taxonomic and trophic variety of epipelagic and mesopelagic species, we show that pelagic species access resources originating from different food sources, mostly autotrophic-based (epipelagics) and microbial heterotrophic-based (mesopelagics). This leads to a sharp trophic dissimilarity between vertical layers. Additionally, we show that trophic specialization increases in deep-sea species and argue that food availability and environmental stability are among the main drivers of this pattern. Finally, we discuss how the ecological traits of pelagic species highlighted in this study can respond to human impacts and increase their vulnerability in the Anthropocene.
Keywords: Biological carbon pump; Environmental stability; Fernando de Noronha archipelago; Microbial trophic pathways; oceanic islands; Stable isotopes